Classification analysis of modern bioreactor systems (review). Part 1. Classification of bioreactors by design parameters - A. A. Dosaev; R. R. Safarov; N. V. Menshutina (Современная наука и инновации)
Bioreactors are an integral part of biotechnological processes. Currently, the scope of their application is expanding and covers many areas of human activity. Bioreactor systems are widely used in biotechnological processes for the production of microorganisms, enzymes, cell lines, viruses, recombinant proteins, as well as various products of the food, cosmetic, pharmaceutical, medical, chemical and agricultural industries. It is worth noting that in addition to being used in production, these devices are used in wastewater and soil treatment processes from various waste at production facilities. Due to the active use of bioreactors, in order to optimize production processes and reduce operating costs, new highly efficient automated devices with a variety of functions are being developed using modern automation technologies, artificial intelligence and 3-D printing. As a result of the presented problem, many scientists and specialists in the scientific field and in production face difficulties in choosing the optimal equipment for performing research and production processes, since large amounts of dispersed data significantly complicate the selection process and require large time and financial resources to search and analyze the necessary information. To solve the problem of data fragmentation, an analysis of scientific papers by domestic and foreign authors on existing types of bioreactors and their classification was carried out. Based on the results of the analysis, this paper presents the first part of the structured information on the classification of bioreactors related to the design features of the devices – classification by design type and appearance. The characteristics of the existing types of bioreactors are given with a description of their structural components and the principle of operation, the advantages and disadvantages of the devices are noted, and examples of their use in various industrial sectors, including in the food industry, are presented. The data, structured based on the results of the analysis of scientific works by domestic and foreign authors, presented in this work, can be used as an auxiliary source of information during the educational process, as well as when performing research work. It is worth noting that the information collected will be used by the authors in the future when conducting a system analysis to develop an information and analytical complex in the field of biotechnological processes using bioreactors.